Convergence Analysis of Parallel S-Iteration Process for System of Generalized Variational Inequalities - D. R. Sahu; Shin Min Kang; Ajeet Kumar (Journal of Function Spaces)
We consider a new system of generalized variational inequalities (SGVI) defined on two closed convex subsets of a real Hilbert space. To find the solution of considered SGVI, a parallel Mann iteration process and a parallel S-iteration process have been proposed and the strong convergence of the sequences generated by these parallel iteration processes is discussed. Numerical example illustrates that the proposed parallel S-iteration process has an advantage over parallel Mann iteration process in computing altering points of some mappings.